(3cQjSJGdjGs 2 (3dMf GdXdGe hGdfhQs - (3YGOd, YHO GdQMefs; (3Nda, YHO GdQMef eMeOs ((3GdbGgQIs (3GdafGQ ddfTQs, 2023)
(3Sjaj hOQYj hQeMj ef CLd obnqHJpc jG cQjSJjdjG, hYOnqhpc GdeLghd bQjH, hCfG MGFlQ CebJ cd gPG, hHjf GdXdGe hGdfhQ dMlf HOjY(B.. (3dcqffj dG Cabg ef CdMGfg TjkFG(B! (3Mjf CLO ELGHGmJ JYjO dj bqhJj CYhO dCchf MGej MeGpc hbGFO LjhTc(B. (3jbhdhf Cf GdSdGe bO CVYa bhGj, dcf CdZGRpc GdeJcQQI gj VYaj, aj GdeGVj HMKoJ Yfpc hGdBf HYO YTQjf YGkeG hLOJpc(B.. (3agd dj HeRjmO ef GdeYQaI?s
Keywords: (3GdCOH GdYQHjs; (3GdbUU GdYQHjIs -- (3eUQs